Elaboration of Integrated Arabic Lesson for Increasing Expertness of Arabic Mastery of Islamic University Students - Yayan Nurbayan, M.A (Intelektual Pustaka Media Utama, 2014)
This study was based on scarcity of Arabic text books which is used in Islamic university. The aim of this study was to produce integrated Arabic textbooks including muthalaa, muhadatsah, kitabah and qiraah in one discourse. This study was using Research and Development method (R and D) started by conception of Integrated Arabic Lesson textbook, followed by limited testing and revision, finished by producing the textbooks pass through revisions and discussions with UPI and UIN Arabic experts and lecturers. This study involved 14 students of STIT and 2 Arabic lecturers of UIN and UPI who were lecturing at that place. It was concluded that competence mean of freshman before using the textbooks were 31, whereas after using it, they got average value 55. The difference was 23.